Association of Tobacco Use and Oral Cancer in a South Asian Population: A Case–control Study - Amra Sultana; Pushpanjali Krishnappa; Vivek Verma; Denny John; K. M. Shwetha; M. M. Sanjana; Anitha R. Sagarkar (Journal of Indian Association of Public Health Dentistry)
Introduction: Cancer is a significant threat to public health both in the developed world and increasingly in developing countries, especially India. The prevalence of oral cancer and oral potentially malignant disorders has shown an increasing trend among the Indian population. Aim: The aim of the study was to assess the risk factors associated with oral cancer among people residing in the field practice area of dental institution. Methods: This is an observational case–control study on 120 adults. Cases were selected from a hospital-based oral cancer registry, and controls were selected from the places where cases were residing. The histological report formed the eligibility criteria for cases registered from 2014 to 2018. Cases and controls were selected at a 1:3 ratio, and group matching was done. Data on exposure were obtained using a standardized tool and analyzed using R software for odds ratio (OR) estimates. The demographic, behavioral factors and tobacco use were compared between the two groups. The Chi-square test was used to compare the categorical variables and independent samples t-test for the continuous variables. Multivariable logistic regression was performed to investigate the association of demographic, clinical, and behavioral factors with the disease. ORs are presented with a 95% confidence interval. In individuals above 60 years, two logistic regression models were compared to investigate the improvement in modeling the association of the independent factors and tobacco use with the occurrence of the disease. Results: Among those more than 60 years of age, OR was higher for smoked form, current user, those using cigarettes, past user, using >5 times in a day, >20 years, and those using betel quid reported higher odds of oral cancer. Across all age groups, smokeless tobacco increased the odds of occurrence of oral cancer by 12 times compared to smoked form at >2 times. In more than 60 years of age group, our findings suggest that smokeless tobacco increased the odds of occurrence of oral cancer by more than 18 times compared to smoked form at >2 times. Being male did not seem to be associated with oral cancer across all age groups and those above 60 years of age. Conclusions: Smokeless tobacco appears to be associated more with the occurrence of oral cancer in adults of all ages and more than 60 years of age in rural population in India.